Strategic Prioritization for State-Owned Airlines Post-Restructuring: A Quantitative Strategic Planning Matrix (QSPM) Analysis of Garuda Indonesia - S. Daniel Kristanto; Ambrosis Romario Latuihamallo; Sylvia Permata Sari; Vania Gosun; Rivan Zulfiano (Green Publisher Indonesia, 2026)
PT Garuda Indonesia as state-owned airlines, post-bankruptcy restructuring has a critical strategic dilemma whether implement aggressive international recovery or focus into domestic dominance. This study aims to formulate and prioritize the optimum strategic direction for PT Garuda Indonesia Tbk after the suspension of debt payment obligations (PKPU). This research used a descriptive quantitative approach based on PT Garuda Indonesia secondary data analysis (2023–2024) and comprehensive strategic management framework by David and David (2022). The strategic formulation process integrates the Input Stage (IFE/EFE and CPM Matrix), Matching Stage (SWOT and IE Matrix) and Decision Stage using the Quantitative Strategic Planning Matrix (QSPM). Garuda Indonesia results in IE Quadrant V (Hold and Maintain), IFE score 2.53 and EFE score 2.83. The QSPM matrix evaluate prioritization strategies preference of Garuda Indonesia where Domestic and Efficiency strategy have a Total Attractiveness Score (TAS) of 6.46, significantly beating the International and Premium Expansion Strategy with TAS: 4.51. This study concludes that in the negative equity positioning and high operational cost, Garuda Indonesia should prioritize on leverage domestic market dominance and optimize cost efficiency rather than premium and international route expansion.